Hubungan antara Status Gizi dengan Maloklusi pada Remaja Usia 14-16 Tahun di SMAN 3 Tuminting - Pangandaheng, Enjelina F.; Anindita, Pritartha S.; Kawengain, Shirley E. S. (e-GiGi, 2026)
Abstract: Malocclusion, or crowded teeth, is frequently encountered across various age groups and can impact individual’s physical and mental health, including chewing function and facial aesthetics. In adolescents, nutritional status plays a role in the development of jaw structure and tooth positioning; however, scientific evidence regarding the relationship between the two still shows varied results. This study aimed to analyze the relationship between nutritional status and the occurrence of malocclusion in adolescents. This was an analytical and observational study with a cross-sectional design. Respondents were 70 adolescents aged 14-16 years at SMA Negeri 3 Tuminting (Senior high school). The results showed that the most frequent age group was 15 years (41.4%), and female students were predominant (58.6%). Most respondents had malocclusion (91.4%). Most repondents had normal nutritional status (68.5%), followed by overweight (14.3%), and underweight and obesity (each of 8.6%). The Fisher’s exact test showed that there was no significant relationship between nutritional status and malocclusion (p=0.657), and the majority of respondents with malocclusion had normal nutritional status. In conclusion, there is no significant relationship between nutritional status based on BMI-for-age and the occurrence of malocclusion among adolescents. Keywords: nutritional status; malocclusion; BMI-for-age; adolescents   Abstrak: Maloklusi atau gigi berjejal merupakan masalah yang sering ditemui di berbagai kelompok usia, dan dapat berdampak pada kesehatan fisik dan mental seseorang, termasuk fungsi pengunyahan dan estetika wajah. Pada remaja, status gizi berperan dalam perkembangan struktur rahang dan posisi gigi, tetapi bukti ilmiah mengenai hubungan keduanya masih menunjukkan hasil beragam. Penelitian ini bertujuan untuk menganalisis hubungan antara status gizi berdasarkan IMT/U dengan kejadian maloklusi pada remaja usia 14–16 tahun. Jenis penelitian ialah analitik observasional dengan desain potong lintang. Responden penelitian ialah 70 remaja usia 14–16 tahun di SMA Negeri 3 Tuminting. Hasil penelitian mendapatkan kelompok usia terbanyak ialah 15 tahun (41,4%) dan jenis kelamin perempuan (58,6%). Sebagian besar responden mengalami maloklusi (91,4%). Responden terbanyak dengan status gizi normal (68,5%), diikuti status gizi gemuk (14,3%), dan status gizi kurus dan obesitas (masing-masing 8,6%). Hasil analisis Fisher’s exact test menunjukkan tidak terdapat hubungan bermakna antara status gizi dan maloklusi (p=0,657), dan mayoritas remaja yang mengalami maloklusi memiliki status gizi normal. Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara status gizi berdasarkan IMT/U dengan kejadian maloklusi pada remaja. Kata kunci: status gizi; maloklusi; IMT/U; remaja